Hepatitis C testing and status among opioid substitution treatment clients in New South Wales - Fiona L. Shand; Carolyn Day; William Rawlinson; Louisa Degenhardt; Nicholas G. Martin; Elliot C. Nelson (Elsevier, 2014)
Abstract Background: In Australia about half of the people who inject drugs (PWID) are hepatitis C (HCV) antibody positive (anti‐HCV+). The prevalence among opioid substitution treatment (OST) clients specifically is unclear, despite OST clinics being a potential setting for HCV care. This study aimed to report the prevalence of HCV among a large sample of NSW OST clients, understand whether HCV testing is translating into knowledge of status, and identify the correlates of inaccurate self‐reporting of HCV status. Methods: Participants completed an interview that included self‐reported HCV status. Participants also provided a blood sample that was tested for HCV IgG antibodies, and for viral load using a quantitative real‐time reverse‐transcriptase polymerase chain reaction. Valid interviews and viable blood sample were provided by 1,484 participants. Logistic regression modelling was used to identify independent predictors of knowledge of HCV antibody status. Results: Overall, 84% of participants were anti‐HCV+. Of these, 65% were RNA+. Four per cent of anti‐HCV negative participants were RNA+. One‐quarter of anti‐HCV+ participants did not know their status or reported it incorrectly, compared with 14.5% of anti‐HCV negative participants. Conclusion: The prevalence of HCV in this sample was higher than that found among other samples of people who inject drugs, suggesting the need for greater prevention efforts with OST clients. Anti‐HCV+ individuals are less accurate at reporting their HCV status than those who are anti‐HCV‐. Inaccurate knowledge is associated with different variables for anti‐HCV+ vs. anti‐HCV‐ individuals. There are opportunities to improve knowledge of HCV status and to therefore improve health outcomes and reduce transmission among this at‐risk population.